Survival Strategies: Socio-Economic Adaptation of River Fishing Communities in the Sebangau Conservation Area - Dhanu Pitoyo; Anisya Nur Widya; Evi Gravitiani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2024)
Sebangau National Park is a conservation area designated by the Indonesian government through the Decree of the Minister of Forestry Number SK.423/Menhut-II/2004. The conversion of the Sebangau area into a conservation area has caused significant changes to the livelihood sources of the people living around the area. This study seeks to examine the socio-economic adjustments of river fishermen within the Sebangau National Park region. Employing qualitative methodologies, the research utilizes data collection techniques that include in-depth interviews and observational methods. Findings indicate that the river fishermen in this area have undergone considerable socio-economic transformations as a result of the establishment of the conservation zone. They must adapt to environmental and economic changes and develop strategies to maintain their livelihoods. This research also found that the role of government and conservation institutions is very important in helping river fishermen adapt to changes in the environment and fishing economy in the Sebangau Katingan National Park Area. The policy implications in the social negotiation space are recognition of community rights, community participation and equality.